SISTEM PENDUKUKUNG KEPUTUSAN PEMILIHAN BARBERSHOP TERBAIK DENGAN MENGGUNAKAN METODE MOORA - Yarma Agustya Dewi Utami; Deci Irmayani; Volvo Sihombing (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Barbershops play a crucial role in maintaining appearance and hairstyles in this modern era. With the continued growth of barbershop businesses in the Bagan Batu area, prospective customers often face challenges in selecting the best barbershop that suits their needs. Therefore, a study was conducted to address the issues faced by potential customers in choosing the best barbershop in the Bagan Batu area. This research involved the development of a Decision Support System (DSS) using the Multi-Objective Optimization by Ratio Analysis (MOORA) method. The criteria considered in this research include location, price, quality, cleanliness, and reputation, each assigned a weight of 0.1; 0.25; 0.25; 0.2; and 0.2, respectively. The data processing results using the MOORA method in this study identified the top 3 barbershop alternatives, namely A6, A8, and A5, with preference values of 0.28945, 0.28135, and 0.28130, respectively. Based on this research, it can be concluded that the Decision Support System using the MOORA method can efficiently assist potential consumers in choosing a barbershop and facilitate the decision-making process in selecting the best barbershop for the Bagan Batu community.